2017
DOI: 10.5114/dr.2017.68778
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation of omega-3 fatty acids in psoriasis

Abstract: Introduction. Omega-3 fatty acids are largely derived from fish oils and are known to decrease inflammation. There have been a few small studies showing the beneficial effect of omega-3 fatty acids in psoriasis.Objective. To evaluate the efficacy of omega-3 fatty acids in conjunction with emollients in patients with mild to moderate chronic plaque psoriasis. Materials and methods.A total of 200 clinically diagnosed cases of chronic plaque psoriasis with less than 10% of body surface area involvement were recru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(29 citation statements)
references
References 21 publications
(59 reference statements)
2
27
0
Order By: Relevance
“…After a drop out of 5 patients in group A and 7 patients in group B, 95 patients and 93 patients completed the study from the two groups respectively ( Table 1). These findings have already been published in a paper by our group [13].…”
Section: Resultssupporting
confidence: 73%
“…After a drop out of 5 patients in group A and 7 patients in group B, 95 patients and 93 patients completed the study from the two groups respectively ( Table 1). These findings have already been published in a paper by our group [13].…”
Section: Resultssupporting
confidence: 73%
“…The application of several scales of disease advancement is extremely important in order to properly assess the therapy efficacy. It must be taken into account that PASI, ‘a golden standard’ constitutes an interpretative challenge due to the fact that there is no linear correlation between PASI value and disease exacerbation, with no account given to patients’ subjective complaints . With regards to BSA, it should be noted that it cannot be treated as an independent index for disease advancement, since it does not take into consideration the morphology of observed changes and may be erroneously overstated …”
Section: Discussionmentioning
confidence: 99%
“…However, after 3 months of treatment, there was not significant differences in PASI decrease in the fish oil group, similarly to the result verified by Soyland, et al [25], where sixty-two plaque psoriasis patients received 6 gr of fish n-3 fatty acids for 4 months. Nevertheless, several studies presented an improvement of the PASI after oral treatment [13] and fish oil infusion [12,26].…”
Section: Discussionmentioning
confidence: 99%
“…The beneficial effects after supplementation with n-3 polyunsaturated fatty acids in psoriasis are still controversial. Some studies have reported improvement in erythema, scaling, infiltration, itching, and area of skin involved [10][11][12][13] as well as reduction in inflammatory markers [10,12], whereas others have not found significant reduction in these parameters [14,15].…”
Section: Introductionmentioning
confidence: 99%